Variables Predicting Academic Success of Nursing Students: a Longitudinal Study in a Nursing Bachelor’s Degree Program - Bulfone, G.; Mazzotta, R.; Cocco, M.; Maurici, M.; Anastasia, M.; Macale, L.; Sili, A.; Vellone, E.; Alvaro, R. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Academic failure can negatively impact on the student, the university and the nursing workforce in the short term. The aim of this study is to analyze the characteristics and predictors of academic success in two cohorts of students of a Nursing Bachelor’s Degree program. Methods. This longitudinal study enrolled students who attended the Nursing Bachelor’s Degree program. The Tor Vergata University includes 21 Nursing Bachelor’s Degree programs at several Sanitary Institutions of the Rome area, with a mean annual recruitment of 800 students. We considered two cohorts of students beginning the program in the 2011-2012 and 2012-2013 academic years, respectively. The follow-up of these two cohorts ended in the 2017-2018 academic year. We considered socio-demographic and academic variables in the nursing field (pre-admission test grade, training exam grade in the first, second and third year and professional license exam grade). The outcome variable is academic success defined as graduation on time; academic failure is defined as changing degree, delay in completion of the course, attrition and dismissal (failure to complete the studies). Data were collected at baseline (T0), at the end of the first year (T1), at the end of the second year (T2) and at the end of the third year (T3) of the course. A logistic regression was performed to identify predictors of academic success. Results. 2,041 students were enrolled, with an average age of 22.0 years (± 4.6, 18-50); 67.4% were female. Regarding academic success, 30.6% of students graduated on time and so achieved academic success, while 69.4% failed to complete the course within the established time: 5.4% (110/2,041) changed the course, the attrition rate was 7.3%, 0.3% (6/2,041) overdue from the course for expiring of the terms, 18.0% (368/2,041) is attending the course and 38.4% (784/2,041) graduated after more than three years. Pre-admission test grade (OR: 10.0, 95% CI: 10.020-10.054) and training exam grade at the second and third years (OR: 10.0 95% CI: 10.027-10.139; OR: 10.2 95% CI: 10.171-10.294) predicted academic success. Discussion and Conclusions. Some nursing students changed course during the last year of the program, while the training exam grade of the second and third years had predicted academic success; this is a brand new information derived from this study. In addition, we confirmed the association of age, gender, secondary school type and grade and preadmission test with academic success. For these reasons, clinical training should be improved and the quality of internship wards, as learning environments, should be monitored. Italian universities should undertake establishing the ideal cut-off in pre-admission tests to determine which students have a high probability of academic success.